OPTIMIZING THE ROLE OF THE FAMILY IN PREVENTING AND HANDLING STUNTING IN THE COVID 19 PANDEMIC - Laviana Nita Ludyanti; Dina Zakiyyatul Fuadah; Dewi Taurisiawati Rahayu (UNUSA Press, 2022)
One of the important foundations in toddlerhood is good and healthy nutritional status. However, there were still many problems with nutritional status at that time, one of which was stunting in toddlers. This condition occurs due to parents' lack of awareness and knowledge regarding the pattern of fulfilling nutrition, especially in toddlers. The lack of awareness and knowledge of mothers about bad parenting practices, the variety of ingredients and the variety of types of food provided to fulfill nutrition in toddlers, and the limited health services, will lead to disruption of the process of growth and development of toddlers, especially brain development. The purpose of this community service activity is to increase parents' role in preventing and treating stunting through increasing parental awareness and knowledge. Community service activities are carried out by educating mothers about efforts to prevent and treat stunting in toddlers. The population of under five is 55 children, with a sample of 17 mothers under five. The results of this community service activity show increased knowledge and awareness of mothers under five about preventing and treating stunting in toddlers, with pretest results of 70.4% and posttest (96%). The results of this community service activity are expected to be reference materials for subsequent community service activities.